Pharmacokinetics of Intravenous, Intramuscular, Oral, and Transdermal Administration of Flunixin Meglumine in Pre-wean Piglets - Kittrell, Heather C.; Mochel, Jonathan P.; Brown, Justin T.; Forseth, Anna Marie K.; Hayman, Kristen P.; Rajewski, Suzanne M.; Coetzee, Johann F.; Schneider, Benjamin K.; Ratliffe, Brette; Skoland, Kristin J.; Karriker, Locke A. (Frontiers in Veterinary Science, 2020)
Castration and tail-docking of pre-wean piglets are common procedures that are known to induce pain and would benefit from pain mitigation. Flunixin meglumine (FM) is a non-steroidal anti-inflammatory drug currently approved in the United States for pyrexia in swine and lameness pain in cattle. The objective of this study was to establish the pharmacokinetic (PK) parameters resulting from intravenous (IV), intramuscular (IM), oral (PO) and transdermal (TD) administration of FM in pre-wean piglets. FM was administered to thirty-nine pre-wean piglets at a target dose of 2.2 mg/kg for IV and IM and 3.3 mg/kg for PO and TD route. Plasma was collected at twenty-seven time points from 0-9 days after FM administration and concentrations were determined using ultra-high performance liquid chromatography coupled with mass spectrometry (UPLC-MS). Pharmacokinetic data were analyzed using noncompartmental analysis (NCA) methods and nonlinear mixed-effects (NLME). Initial plasma concentration for IV (C0) 11653 µg/L and mean peak plasma concentrations (Cmax) 6543 µg/L (IM), 4883 µg/L (PO), and 31.5 µg/L (TD) were measured. The time points of peak FM concentrations (tmax) were estimated 30 min, 1 hr, and 24 hrs for IM, PO, and TD, respectively. The bioavailability (F) of PO and IM FM was estimated at greater than 99%, while the bioavailability of TD FM was estimated to be 7.8%. The reported Cmax of FM after IM and PO administration is consistent with therapeutic concentration ranges that mitigate pain in other species and adult pigs. However, the low estimated concentration of FM after TD dosing is not expected to mitigate pain in pre-wean piglets. The low F of TD FM suggests that expanding the surface area of application is unlikely to be sufficient to establish an effective TD dose for pain, while the high bioavailability for PO FM should allow for an effective dose regimen to be established.